Entrepreneurial Socialization and Psychological Capital: Cross-Cultural and Multigroup Analyses of Impact of Mentoring, Optimism, and Self-Efficacy on Entrepreneurial Intentions. (January 2019) - Baluku, Martin M.; Matagi, Leonsio; Musanje, Khamisi; Kikooma, Julius Fred; Otto, Kathleen
This study demonstrates that psychological capital is essential in the process of developing and strengthening entrepreneurial intentions. We specifically investigate the mediating roles of optimism and self-efficacy facets of psychological capital in the relationship between entrepreneurial mentoring and intentions. The study was conducted among 1, 272 young persons from Germany and East Africa (Uganda and Kenya). These included 784 final year university students and 488 wage employed. A multigroup analysis was applied to test for the effects of employment status and country differences. Results indicate that mentoring, optimism, and self-efficacy are positively correlated with entrepreneurial intentions. Findings also supported the hypothesized-mediated mediation model that mentoring impacts on entrepreneurial intentions through optimism and self-efficacy. The association of entrepreneurial mentoring on intentions was higher among the Germany participants than in the East African sample as well as among the students compared with employed individuals. Practical and theoretical implications of our findings are discussed.